PENERAPAN METODE QOS UNTUK EVALUASI JARINGAN INTERNET DI ITEBIS PGRI DEWANTARA JOMBANG - Tofan Putra Irianto; Chamdan Mashuri (Fakultas Teknologi Informasi, 2025)
The internet has become a very vital infrastructure in supporting various academic and administrative activities in higher education. This research aims to evaluate the performance of the internet network at ITEBIS PGRI Dewantara Jombang using the Quality of Service (QoS) method, which includes measuring parameters such as Throughput, Delay (Latency), Packet Loss, and Jitter. The application of the QoS method proved effective in providing a clear picture of network performance, which was measured in various campus locations such as PPSI, Library, and KPM. Using a web-based application developed with the Laravel framework, network performance data can be managed and visualized easily, allowing Admins and Heads to manage and monitor network service quality in real-time. The results show that locations such as PPSI have excellent service quality with an average index value of 3.5, while other locations such as the Library and KPM have sufficient service quality with an average index value of 2. Although the available bandwidth is quite large, problems such as uneven traffic distribution or sub-optimal configuration need to be fixed to improve service quality in some locations.